Bioinspired Protein/Peptide Loaded 3D Printed PLGA Scaffold Promotes Bone Regeneration - Song, Xiaoliang; Li, Xianxian; Wang, Fengyu; Wang, Li; Lv, Li; Xie, Qing; Zhang, Xu; Shao, Xinzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: This study was aimed to investigate the effect of three dimensional (3D)printed poly lactide-co-glycolide (PLGA) scaffolds combined with Gly-Phe-Hyp-Gly-Arg (GFOGER) and bone morphogenetic protein 9 (BMP-9) on the repair of large bone defects. Methods: 3D printing method was used to produce PLGA scaffolds,and the sample was viewed by both optical microscopy and SEM, XRD analysis, water absorption and compressive strength analysis, etc. The rabbits were divided into six groups randomly and bone defect models were constructed (6 mm in diameter and 9 mm in depth): control group (n=2), sham group (n=4), model group (n=4) and model +scaffold group (n=4 rabbits for each group, 0%,2% and 4%). The rabbits were sacrificed at the 4th and 12th weeks after surgery, and the samples were collected for quantitative analysis of new bone mineral density by micro-CT, histopathological observation, immunohistochemistry and Western blot to detect the protein expression of osteoblast-related genes. Results: This scaffold presented acceptable mechanical properties and slower degradation rates. After surface modification with GFOGER peptide and BMP-9, the scaffold demonstrated enhanced new bone mineral deposition and density over the course of a 12 week in vivo study. Histological analysis and WB confirmed that this scaffold up-regulated the expression of Runx7, OCN, COL-1 and SP7, contributing to the noted uniform trabeculae formation and new bone regeneration. Conclusions: The application of this strategy in the manufacture of composite scaffolds provided extensive guidance for the application of bone tissue engineering.